Reviving Ancient Splendor: Graphic Restoration of the Mosque of Odina in Uzbekistan - Elvira Jurayeva; Luqmonov Dilshod; Odina Olimova (Indonesian Journal of Cultural and Community Development, 2024)
This study delves into the graphic restoration of the historic mosque of Odina in Karshi, Uzbekistan, as part of broader efforts to preserve and repair architectural treasures in post-independence Uzbekistan. Utilizing archival data, historical sources, and scientific research, the study aims to recreate the original appearance and architectural elements of this significant monument. Through meticulous analysis and reconstruction, the project yields detailed insights into the early aesthetics; and construction techniques of the mosque, contributing valuable knowledge to the global discourse on heritage conservation and historical architecture. Higlights: Graphic restoration techniques employed archival data, historical sources, and scientific research for authenticity. The study focuses on recreating the original appearance and architectural elements of the historic mosque of Odina in Karshi, Uzbekistan. Insights gained contribute to global discussions on heritage conservation and historical architecture. Keywords: Mosque Restoration, Historical Preservation, Architectural Heritage